Clear air turbulence over south Asia and neighbourhood - MUKHERJEE, A. K.; DANIEL, C. E. J.; THIRUVENGADATHAN, A.; BALACHANDRAN, K. (MAUSAM, 1976)
Over 9000 aircraft reports have been studied to estimate the frequency or occurrence or Clear Air Turbulence (CAT) along various routes diverging from Bombay and to assess the usefulness or the Richardson's number (Ri) in the identification or areas favorable for CAT occurrence. It is round that for smaller layers Ri 13 can be a useful indicator or CAT prone areas. It is also observed that among the different air routes emanating from 2 Bombay, the Bombay-Aden and Bombay-Bangkok routes show the highest frequency or CAT occurrence. The stability factor in Ri is of considerable importance at lower latitudes as the variation or potential temperature with height near the normal jet flight levels in this area is small enough to produce Ri less than 1 even with comparatively tern less wind shear. A monogram for easy and quick examination or the 300, 250 and 200 rob levels for prediction of areas susceptible to CAT has been suggested.